Pilea cadierei Aluminum Plant: FPS478/FP478, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the Pilea cadierei, commonly known as the aluminum plant. It describes the plant’s distinctive variegated foliage, growth habits, and care requirements. The aluminum plant thrives in shaded areas and can be used as a ground cover, in hanging baskets, or cascading down walls. It is sensitive to pests and requires regular irrigation and fertilization to maintain its appearance. The document also highlights the plant’s invasive potential and its suitability for USDA hardiness zones 10 through 11. Original publication date October 1999.